2019
DOI: 10.1111/cmi.12979
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: MiRNA‐218 regulates osteoclast differentiation and inflammation response in periodontitis rats through Mmp9

Abstract: Periodontitis is a multiple infection and inflammatory disease featured by connective tissue homeostasis loss, periodontal inflammation, and alveolar bone resorption. MicroRNAs (miRNAs) are involved in the mediation of a large scale of pathological processes. Here, we show that miRNA‐218 provides protective effect on periodontitis via regulation of matrix metalloproteinase‐9 (Mmp9). This pathway is aberrant in periodontium from rats with periodontitis and human periodontal ligament progenitor cells stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Related study confirmed that miR‐218 suppressed the progression of cervical cancer via the LYN/NF‐κB signalling pathway (Xu, et al , 2018). In addition, miR‐218 plays an important role in regulating the osteoclast differentiation and inflammation response in rats with periodontitis (Guo, et al , 2019) and the development of human natural killer cells (Victor, et al , 2018). Here, miR‐218 suppressed the activation of NF‐κB and the LPS‐induced secretion of TNF‐α, IL‐1β and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…Related study confirmed that miR‐218 suppressed the progression of cervical cancer via the LYN/NF‐κB signalling pathway (Xu, et al , 2018). In addition, miR‐218 plays an important role in regulating the osteoclast differentiation and inflammation response in rats with periodontitis (Guo, et al , 2019) and the development of human natural killer cells (Victor, et al , 2018). Here, miR‐218 suppressed the activation of NF‐κB and the LPS‐induced secretion of TNF‐α, IL‐1β and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), small noncoding RNAs rarely translated into peptides or protein, are of great importance in multiple biological processes and various kinds of disease . Several studies have proved that miRNAs could be critical regulators in bone remodeling and inflammatory response such as periodontitis . The aberrant miRNA expression reacting to pathologic products, in turn, affects periodontitis .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several studies have proved that miRNAs could be critical regulators in bone remodeling and inflammatory response such as periodontitis. [8][9][10] The aberrant miRNA expression reacting to pathologic products, in turn, affects periodontitis. [9][10][11] In our previous studies, it has been shown that microRNA-335-5p (miR-335-5p) could promote osteoblast differentiation and bone regeneration in vitro and in miR-335-5p transgenic (335-Tg) mice via inhibiting DKK1, a Wnt pathway antagonist, which have been well-characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, miR-218-5p has been stated to promote osteogenic differentiation of MSCs in mice (41) and increase bone formation by targeting WNT pathway inhibitors, (42) all the while also negatively regulating osteoclastogenesis through RANKL, Mmp9, and NF-κB. (43,44) Of note, we have recently published findings of elevated serum Dickkopf-1 (DKK1; dickkopf WNT signaling pathway inhibitor 1) concentrations in these same PLS3 mutation-positive subjects. (45) DKK1 is an osteocyte-derived inhibitor of the WNT pathway in bone.…”
Section: Discussionmentioning
confidence: 87%